Implementasi Kebijakan Tentang Angka Putus Sekolah Pada Kota Sukabumi - Sutisna, Ateng; Nur Azizah, Dawia; Rachmawati, Ike (Dinasti Research, 2025)
This study aims to analyze the implementation of policies to address the school dropout rate (APS) in Sukabumi City. Although the APS at the elementary/Islamic elementary school (SD/MI) level is almost negligible, problems persist at the junior high/Islamic junior high school (SMP/MTs) level, particularly in areas with high socio-economic vulnerability. The research employs a descriptive qualitative approach, utilizing primary data from interviews with the Head of the Education and Culture Office of Sukabumi City and secondary data from official documents and local media. The findings reveal that the causes of APS include economic constraints, low learning motivation, early marriage, administrative barriers, and cultural influences. Strategies implemented include the School Dropout Tracking Program (PAPS), family mentoring, equivalency education, and mapping of APS-prone areas involving various stakeholders. Challenges encountered include data accuracy and integration, cultural resistance, and the impact of class quota policies on private schools. Assistance programs such as BOS, PIP, and Smart Cards play a role in preventing APS but have not yet been fully optimized. This study recommends strengthening area-based data systems, improving the effectiveness of educational assistance, fostering program innovation, and empowering communities to ensure equitable access to education.